1990
DOI: 10.1017/s0017383500028965
|View full text |Cite
|
Sign up to set email alerts
|

A Stranger in Town: Finding the Way in an Ancient City

Abstract: My subject concerns the practicalities of finding one's way round an ancient city. What aids were there to guide a stranger in town? How did he trace a particular house or other destination? I propose to examine the problem with reference to one of the best known of all ancient cities, Pompeii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Certainly, the authors of the slave collars appear to have assumed that the larger regions were a safer bet. The expectation appears to have been that the reader could be relied upon to find the region, and would then ask its residents for the specific slave-owner or location named on the collar (Ling, 1990; Bérenger, 2008). This system implies in turn that the people living in each region typically had a working knowledge of its major local families and landmarks, allowing them to identify the place or person specified.…”
Section: Living In the Regionsmentioning
confidence: 99%
“…Certainly, the authors of the slave collars appear to have assumed that the larger regions were a safer bet. The expectation appears to have been that the reader could be relied upon to find the region, and would then ask its residents for the specific slave-owner or location named on the collar (Ling, 1990; Bérenger, 2008). This system implies in turn that the people living in each region typically had a working knowledge of its major local families and landmarks, allowing them to identify the place or person specified.…”
Section: Living In the Regionsmentioning
confidence: 99%
“…Only a limited number of studies, in contrast, have considered the topic of pedestrian movement dynamics. Early research focused upon questioning what factors within an ancient urban landscape guided pedestrian activity (MacDonald, 1986;Ling, 1990). At Pompeii, research has identified and shown how specific urban features such as street-side benches and tabernae (shops) structured movement along the city's streets (Ellis, 2004;Hartnett, 2008).…”
Section: Reframing Processional Movement Studymentioning
confidence: 99%
“…It was these small districts that provided the social cohesion in the city. Larger streets, districts and gates at Rome usually had names, but since there were no signs or house numbers, that was not much of a help to a stranger (Dilke 1985: 103-107;Ling 1990a). Instead, the vici became very important for urban navigation, and were often used for directions.…”
Section: Districtmentioning
confidence: 99%
“…Apart from these ad hoc signboards, shops could also have proper ones. The Digest (50.16.245) speaks about 'pictures attached by chains or fi xed to a wall, or lamps similarly fi xed', and several brick plaques, fi gurative or geometric, have been found in Pompeii and Ostia, advertising different trades and crafts (Ling 1990a;Ling 1990b;Butterworth and Laurence 2005: 55, 110). These could surely work as small landmarks, guiding the traveller (Figs.…”
Section: Entering the Marble Planmentioning
confidence: 99%